The Potential Vector Competence and Overwintering of West Nile Virus in Vector Aedes Albopictus in China - Zhang, Ying-mei; Guo, Xiao-xia; Jiang, Shu-fang; Li, Chun-xiao; Xing, Dan; Zhang, Heng-duan; Dong, Yan-de; Zhao, Tong-yan (Frontiers in Microbiology, 2022)
West Nile virus (WNV) is a widespread zoonotic arbovirus and a threat to public health in China since its first isolation in 2011 in Jiashi County, Kashgar Region, Xinjiang of western China. Determining the vector competence of WNV infection has important implications for the control of disease outbreaks. To assess the risk that indigenous mosquitoes in China are capable of transmitting and sustaining West Nile virus (WNV), four Aedes albopictus mosquito strains were allowed to feed on the artificial infectious blood meal with WNV dose of 106.7-106.9 plaque-forming unit/ml and tested two weeks later to determine infection and transmission rates. The results indicated that four strains Ae. albopictus mosquitoes were competent laboratory vectors of WNV. The infection rates of different strains ranged from 16.7 to 60.0% and were statistical differences (x2=12.81，p<0.05).The highest infection rate was obtained with Shanghai strain (60.0%).The Leghorn chicken that has been bitten by infectious mosquitoes can be infected with the virus, which is direct evidence that this mosquito species can transmit WNV and is a potential vector. Furtherly，the present study confirmed that WNV could survive in the diapause eggs of Ae. albopictus and be transmitted transstadially to progeny after diapause termination. This is of great significance for clarifying that West Nile virus maintains its natural circulation in harsh environments through inter-epidemic seasons.